Otherness in interior identity: a reflection about the Freudian concepts of unconscious, superego, and Id - Oliveira Moreira, Jacqueline De (The Spanish Journal of Psychology, 2008)
Theoretical, psychoanalytical constructs referring to the unconscious, the superego, and id, enjoy an autonomy within the I. As such, this study contemplates the discussion of these foreign entities that inhabit the interior of the I, producing an effect of foreignness. In the first section, I will develop a reflection on the state of foreignness of the unconscious. I will begin with an analogy used by Freud, which addresses the thesis of universality of consciousness with the psychoanalytical thesis of the subconscience within the I. Affirmation of consciousness in the other may be used analogously for affirm the idea of another inhabiting our own being. I shall continue, seeking to understand how the process of unconscious repression produces the effect of foreignness. The idea of a moral censor present in the entity of the superego constitutes the theme of the second section. The superego follows the principle of otherness in its constitution and in its effects on the I. Finally, a reflection on the dimension of otherness in the Id seems urgent to me, as with this concept, Freud radicalized in the idea of the foreign as the origin of the subject.